2007
DOI: 10.1016/j.jneuroim.2006.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic neurotransmitters modulate immunoglobulin A secretion in porcine colonic mucosa

Abstract: Secretory immunoglobulin A (sIgA) plays a crucial role in mucosal surface defense. We tested the hypothesis that colonic sIgA secretion is under enteric neural control. Immunohistochemistry of the porcine distal colonic mucosa revealed presumptive cholinergic and adrenergic nerve fibers apposed to secretory component (SC)-positive crypt epithelial cells and neighboring IgA + plasmacytes. The cholinomimetic drug carbamylcholine elicited rapid, atropine-sensitive IgA secretion into the luminal fluid bathing muco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 35 publications
1
31
1
Order By: Relevance
“…The CNS can modulate the activity of the autonomic nervous system (the adrenergic and cholinergic nervous system) and evoke the neuronal release of norepinephrine (NE), acetylcholine (ACh) and other neurotransmitters in peripheral tissues, including the intestinal mucosa (Felten, Felten et al 1987;Kulkarni-Narla, Beitz et al 1999;Kohm and Sanders 2001;Tracey 2002;Green, Lyte et al 2003;Pavlov, Wang et al 2003;Sternberg 2006;Sanders and Kavelaars 2007;Schmidt, Xie et al 2007;Chrousos 2009;Kvetnansky, Sabban et al 2009). These mediators may influence the function of the intestinal mucosa and its associated surface bacterial populations.…”
Section: Role Of the Autonomic Nervous System In The Immune Response mentioning
confidence: 99%
See 3 more Smart Citations
“…The CNS can modulate the activity of the autonomic nervous system (the adrenergic and cholinergic nervous system) and evoke the neuronal release of norepinephrine (NE), acetylcholine (ACh) and other neurotransmitters in peripheral tissues, including the intestinal mucosa (Felten, Felten et al 1987;Kulkarni-Narla, Beitz et al 1999;Kohm and Sanders 2001;Tracey 2002;Green, Lyte et al 2003;Pavlov, Wang et al 2003;Sternberg 2006;Sanders and Kavelaars 2007;Schmidt, Xie et al 2007;Chrousos 2009;Kvetnansky, Sabban et al 2009). These mediators may influence the function of the intestinal mucosa and its associated surface bacterial populations.…”
Section: Role Of the Autonomic Nervous System In The Immune Response mentioning
confidence: 99%
“…However, little is known about the neuroendocrine regulation of intestinal IgA (Schmidt, Eriksen et al 1999;Schmidt, Xie et al 2007;Reyna-Garfias, Miliar et al 2010).…”
Section: Neuroendocrine Regulation Of Intestinal Iga and Protection Amentioning
confidence: 99%
See 2 more Smart Citations
“…Schmidt et al showed that exogenous administration of catecholamines to ex vivo constructs of polarized pig intestinal tissue caused significantly more IgA to be secreted into the apical supernatant. 97 Whether this effect was direct, or mediated by some other secondary signal (like a cytokine) is unknown.…”
Section: Injury and Mucosal Immunitymentioning
confidence: 99%